The lasting impact of mothers' fetal malnutrition on their offspring: Evidence from the China great leap forward famine - Seonghoon Kim; Quheng Deng; Belton M. Fleisher; Shi Li (Institute for the Study of Labor (IZA), 2010)
We find that second-generation effects of in utero and early childhood malnutrition on the school participation of the offspring of mothers who experienced the China Great Leap Forward Famine. The direct impact on entrance to senior high school is also negative, but smaller in magnitude than that on entrance to junior high school. Given that entering senior high school is contingent on completion of junior high school, the direct impact on entrance to senior high school obviously understates the total impact on the second generation's accumulation of human capital. Our estimation results are generally robust to IV estimation.
Keywords: I12; J16; P36; 330; malnutrition; health; schooling; Barker hypothesis; China Famine; Mütter; Unterernährung; Kinder; Gesundheit; Bildungsniveau; China